The Concept of Ownership and Property in Islam - Nurlina, Nurlina; Wahab, Abdul; Lutfi, Mukhtar (Jurnal Ar-Ribh, 2022)
This study aims to determine how the concept of property ownership, the application of property in Islamic economics and to analyze Afzalur Rahman's thoughts on the concept of property ownership in Islamic economics. The method used by the author in this study is library research based on the problem formulation supported by data and data sources from a literature review. Based on the results of research on the concept of property ownership in Islamic economics, according to Afzalur Rahman, an Islamic economic system is comparable to economic principles that require an economic system that is in accordance with the Qur'an and As-Sunnah. Where Islam also wants everyone who has property in the form of goods or services obtained in a lawful way, both in the form of substances and how to get them, does not damage and damage human nature, nor does persecution and exploitation, the goal in the end is to fight for the needs of human life and seek the pleasures of the hereafter that are blessed by Allah SWT.